2010
DOI: 10.4258/hir.2010.16.3.158
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Daily Patient Numbers for a Regional Emergency Medical Center using Time Series Analysis

Abstract: ObjectivesTo develop and evaluate time series models to predict the daily number of patients visiting the Emergency Department (ED) of a Korean hospital.MethodsData were collected from the hospital information system database. In order to develop a forecasting model, we used, 2 years of data from January 2007 to December 2008 data for the following 3 consecutive months were processed for validation. To establish a Forecasting Model, calendar and weather variables were utilized. Three forecasting models were es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 18 publications
1
48
1
1
Order By: Relevance
“…Sun et al (2009) established ARIMA models to predict daily attendance at an ED. Kam (2010) used seasonal ARIMA to predict daily number of patient visits to ED. ARIMA was constructed to predict ED visitor volume in Chen et al's study (2011).…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al (2009) established ARIMA models to predict daily attendance at an ED. Kam (2010) used seasonal ARIMA to predict daily number of patient visits to ED. ARIMA was constructed to predict ED visitor volume in Chen et al's study (2011).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, SARIMA models have been successfully employed to predict the incidence or death trends of malaria 11 and pneumonia 12 or daily patient numbers. [13][14] The principal objective of our study was to construct a SARIMA model by which the reported JE incidence in Xianyang, Shaanxi, China could be predicted. The findings of this study will be useful for forecasting JE epidemics and providing valuable reference information for JE control and prevention in Xianyang City and even throughout China.…”
mentioning
confidence: 99%
“…MAPE represents the relative scale of the prediction error between the forecasted value, which is a series variable, and the observed value; the smaller the error is, the more accurate the prediction is (Kam et al, 2010). Besides, it is valid for MAD and MSD; the smaller MAD and MSD are, the more accurate the prediction is.…”
Section: Methods Evaluationmentioning
confidence: 99%
“…Schweigler et al (Schweigler et al, 2009) showed that the models using time series methods generate more accurate shortterm forecasts of Emergency Department (ED) bed occupancy than using traditional historical averages models. Kam et al (Kam et al, 2010) developed and assessed three time series models to predict the daily number of patients visiting the ED of a Korean hospital. The results show that the multivariate SARIMA model exhibits high reliability and forecasting accuracy compared to other models.…”
Section: Introductionmentioning
confidence: 99%